KEMAMPUAN LITERASI MATEMATIKA SISWA SEKOLAH DASAR BERDASARKAN PRESPEKTIF TEORI GESTALT - Syah, Mohamad Sabilli Firman; Widodo, Wahono; Sudibyo, Elok (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Mathematical literacy It is important to have and improve early on students at the elementary school level. Mathematical literacy is related to students' ability to interpret mathematics in various contexts in life. The purpose of this research was to examine the literacy level of elementary school students in Indonesia based on the gestalt theory. This research method uses Literature Review (LR). Data collection was carried out by reviewing all articles related to students' literacy skills that were published in the 2016-2023 period. This research examines 35 indexed national journal articles obtained through the Google Schoolar database using the Harzing Publish or Perish application. The results of this research show that the mathematical literacy skills of elementary school students are very diverse. Based on the Gestalt theory, the diversity of students' mathematical literacy abilities is due to the different insights of each individual. To increase students' insight into mathematical literacy, they can apply learning models that make students active, learning that integrates mathematics in the context of students' daily lives, and habituation activities to work on mathematical literacy type questions.